MANAJEMEN STRATEGI PENINGKATAN MUTU PENDIDIKAN DI MADRASAH PADA MASA PANDEMI COVID-19 - Susanah Susanah; Irawan Irawan; Ari Prayoga (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2021)
This study aims to reveal the strategic management planning for improving the quality of madrasah education during the Covid-19 pandemic and the development of the learning curriculum at Madrasah Aliyah 2 Nagreg. The approach used in this research is qualitative descriptive method. Data collection techniques used include: observation, interviews, survey, and documentation studies. The results of the research show that planning for improving the quality of education during the Covid-19 pandemic is developing a learning curriculum at Madrasah Aliyah 2 Nagreg, namely formulating madrasah vision and mission, setting educational goals in accordance with national education goals and forming a curriculum development team by involving relevant stakeholders in improving the quality of education. The SWOT analysis result of the survey shows the results of the Total analysis score Strength = 19.0 Weakness analysis score = 13.4 Opportunity analysis score = 4.0 and Threat analysis score = 1.8 for the analysis score Organization position graph X = 5.66 and Y = 2.23 is in quadrant I with steps to support aggressive strategies. The curriculum developed during the Covid-19 pandemic was developed with the emergency curriculum standard of the Indonesian Ministry of Religion.